2006
DOI: 10.1038/nmat1650
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional composites using reinforced laminae with carbon-nanotube forests

Abstract: Traditional fibre-reinforced composite materials with excellent in-plane properties fare poorly when out-of-plane through-thickness properties are important. Composite architectures with fibres designed orthogonal to the two-dimensional (2D) layout in traditional composites could alleviate this weakness in the transverse direction, but all of the efforts so far have only produced limited success. Here, we unveil an approach to the 3D composite challenge, without altering the 2D stack design, on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
405
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 681 publications
(418 citation statements)
references
References 14 publications
3
405
1
Order By: Relevance
“…The F-CFRP and, to a lesser degree, the CFRP displays decreasing fracture toughness with respect to crack length, whereas the SR-CFRP data displays stable behaviour Typically, for fracture toughness testing, the initial values and propagation values at steady state are compared. Veedu et al [54] opted to compare only the initial fracture toughness values of their SiC fibres (plain weave) modified with CNTs, stating that these initiation values represent the generic fracture toughness and Prel et al [55] suggested that initiation values for fracture toughness are independent of sample thickness. Garcia et al [56] also observed reduction in fracture toughness with crack length for their CNT-modified samples and attributed this to the discontinuous placement of CNTs on the cross ply (although this is not the case in the present work, see Figure 2).…”
Section: Interlaminar Fracture Toughnessmentioning
confidence: 99%
“…The F-CFRP and, to a lesser degree, the CFRP displays decreasing fracture toughness with respect to crack length, whereas the SR-CFRP data displays stable behaviour Typically, for fracture toughness testing, the initial values and propagation values at steady state are compared. Veedu et al [54] opted to compare only the initial fracture toughness values of their SiC fibres (plain weave) modified with CNTs, stating that these initiation values represent the generic fracture toughness and Prel et al [55] suggested that initiation values for fracture toughness are independent of sample thickness. Garcia et al [56] also observed reduction in fracture toughness with crack length for their CNT-modified samples and attributed this to the discontinuous placement of CNTs on the cross ply (although this is not the case in the present work, see Figure 2).…”
Section: Interlaminar Fracture Toughnessmentioning
confidence: 99%
“…PVDF experiences high deformations when subjected to changes in temperature due to its high coefficient of thermal expansion (CTE, α = 127 × 10 −6 K −1 ), which easily generates internal stress in laminated films containing a PVDF layer 21. Carbon materials (e.g., single‐walled carbon nanotube (SWCNT), graphene oxide (GO)) have negative CTEs (α = −1.5 × 10 −6 and −67 × 10 −6 K −1 , respectively), which means that these materials contract whereas PVDF expands when the environmental temperature increases 22. As far as moisture absorption is concerned, both PVDF and carbon material expand when they take up water 23.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include 1D flexible yarns, 5,6 2D sheets, 7 3D "mats" or "forests" of aligned CNTs, [8][9][10] and disordered structures. 11 These systems have been suggested for several applications, including electronic 11,12 and field emission devices, 13 composites, 14,15 and bioactive materials. 16,17 The partial anchoring of vertical arrays of carbon nanotubes (VACNTs) in a single, thin polymer film has been previously reported, 18,19 and the mechanical response of anchored VACNTs has been characterized under quasi-static compressive loading.…”
Section: Introductionmentioning
confidence: 99%